2021
DOI: 10.21037/atm-20-5320
|View full text |Cite
|
Sign up to set email alerts
|

The interval between onset and admission predicts disease progression in COVID-19 patients

Abstract: Background: The prognostic role of the interval between disease onset and hospital admission (O-A interval) was undetermined in patients with the coronavirus disease 2019 (COVID-19). Methods: A total of 205 laboratory-confirmed inpatients admitted to Hankou hospital of Wuhan from January 11 to March 8, 2020 were consecutively included in this retrospective observational study. Demographic data, medical history, laboratory testing results were collected from medical records. Univariate and multivariate logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Consistent with our findings, previous research has shown that delayed hospital admissions correlate with prolonged SARS‐CoV‐2 RNA shedding time 17 . Moreover, prior research indicates that patients with early hospital admissions experience milder COVID‐19 progression 25 . Taken together, these findings underscore the importance of individuals seeking immediate hospital care upon confirmation of SARS‐CoV‐2 infection.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, previous research has shown that delayed hospital admissions correlate with prolonged SARS‐CoV‐2 RNA shedding time 17 . Moreover, prior research indicates that patients with early hospital admissions experience milder COVID‐19 progression 25 . Taken together, these findings underscore the importance of individuals seeking immediate hospital care upon confirmation of SARS‐CoV‐2 infection.…”
Section: Discussionsupporting
confidence: 91%
“…Peng et al reported that the O-A interval less than 7 days predict the likelihood of disease progression in moderate-severe disease Covid 19. 27 But limitations were stated in aforementioned study that the health-seeking behavior of the patient and the domestic health system might influence the admission interval, aside from selection bias and confounding factors.…”
Section: Resultsmentioning
confidence: 95%
“…Other studies have shown that prone position may be more effective when performed early than later [10,43]. It has also been shown that the earlier patients are admitted to hospital for intervention, the less likely mild and moderate cases will progress to severe and critical [44]. However, there are few studies concerning whether it is possible to reduce the percentage of conversion to severe and critical cases if prone position was performed on the day of admission in mild and moderate patients.…”
Section: Discussionmentioning
confidence: 99%